2020
DOI: 10.1155/2020/8121395
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association between Poor Glycemic Control in T2DM and Subclinical Hypothyroidism

Abstract: Background. Hypothyroidism is a highly prevalent and multifactorial disorder and has been implicated in the causation of dyslipidemia, dermatological diseases, atherosclerosis, and myocardial dysfunction, as well as endothelial dysfunction. The relationship between subclinical hypothyroidism and type 2 diabetes mellitus is not well established. In the present study, we attempt to find out the prevalence of subclinical hypothyroidism in type 2 diabetes mellitus and its association with glycemic control. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Sharma and cols. (2020) reported that patients with diabetes and subclinical hypothyroidism have similar glycemic control as patients with only diabetes ( 38 ), and Mehalingam and cols. (2020) reported that patients with both diseases did not present more severe complications of diabetes compared to patients with only diabetes ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sharma and cols. (2020) reported that patients with diabetes and subclinical hypothyroidism have similar glycemic control as patients with only diabetes ( 38 ), and Mehalingam and cols. (2020) reported that patients with both diseases did not present more severe complications of diabetes compared to patients with only diabetes ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Os autores pontuaram que esse efeito foi mais forte em indivíduos com 65 anos ou mais quando comparado aos mais jovens (Chen et al, 2007;Cho et al, 2016;Elgazar et al;. Entretanto, em contraste com os estudos anteriores, Sharma et al (2020) relatou em uma pequena amostra de pacientes com diabetes que aqueles que apresentavam diabetes e hipotireoidismo subclínico tinham um controle glicêmico similar aos que apresentavam apenas diabetes (Sharma et al, 2020) e a análise de Mehalingam et al (2020) em 331 pacientes com diabetes mostrou que a presença do hipotireoidismo subclínico não foi associado com complicações mais graves do diabetes em pacientes com ambas as doenças (Mehalingam et al, 2020).…”
Section: Discussionunclassified